(untitled) (Biological Sciences - PJSIR, 2004)
The extracts of Artemisia absinthium induced a significant decrease in volume of gastric juice, acid output and peptic activity but no effect was determined on mucin activity in acetylsalicylic acid (ASA) ulcerated rats. Moreover, they decreased the ulcer index significantly. Phytochemical analysis indicated the presence of saponins and glycosidic sugars in the extract.